Adsorptive Desulfurization of Model Gasoline Using Attapulgite and Acid-Treated Attapulgite Adsorbents - Jiang, Ruiyu; Zhang, Jiling; Yu, Shuanglin; Tang, Zhe (Asian Journal of Chemistry, 2015)
The objective of this work is to examine the performance of raw attapulgite and acid treated attapulgite for adsorptive desulfurization of model gasoline at room temperature. The effect of the inner structures of the adsorbent on sulfur removal efficiency was discussed. Several analytical instruments were used to analyze the adsorbents. The results indicated that the raw attapulgite had the greatest affinity for thiophene, which may be ascribed to the complicated and blocked mesoporous structure and more adsorptive activated sites on its surface.